Dampak Revolusi Industri 4.0 Era Covid-19 pada Sistem Informasi Akuntansi Terhadap Struktur Modal Perusahaan - Hertati, Lesi; Safkaur, Otniel (Jurnal Riset Akuntansi dan Keuangan, 2020)
The impact of the Covid-19 era 4.0 revolution on accounting information systems is to produce data that is integrated with each other. Information systems that are accurate and well-accommodated in the Covid-19 era reflect correct knowledge and behavior so that important elements of the flow of financial business funds can be accommodated in a timely manner through the information system network to the sub-system sections. Accounting information systems are quite important in the capital market in order to provide information about the optimal capital structure for decision making. Capital structure activities carried out in a company have their own objectives, as well as in the process of making company financial reports. In general, corporate financial reports are a medium for a company's financial information. Either for financial information that is prepared under special conditions or also reports that are prepared at certain times on a regular basis. For reports prepared in these special conditions, the data analysis technique uses the Structural Equation Modeling (SEM) technique, involving 1,245 employees of PT Freeport Indonesia and 412 samples collected from employees. The results showed that the accounting information system had an effect on the company's capital structure. Financial statement analysis can be carried out effectively and efficiently where financial statements are used with analytical methods and techniques to determine and measure the relationship between items in the financial statements, so that changes in each item can be seen when compared. This research was conducted at PT Freeport Indonesia which is based in Papua.Abstrak. Dampak revolusi 4.0 era covid-19 pada  sistem informasi akuntansi adalah menghasilkan data secara terintegrasi satu sama lain. Sistem informasi yang akurat dan dan terakomodir dengan baik  era covid-19 adalah mencerminkan pengetahuan dan perilaku yang benar sehingga elemen penting  dari aliran dana bisnis keuangan dapat terakomodir dengan tepat waktu  melalui jaringan sistem informasi ke bagian sub-sub sistem. Sistem Informasi akuntansi cukup penting dalam pasar modal guna memberikan informasi tentang struktur modal yang optimal guna pengambilan keputusan. Aktivitas struktur modal yang dilakukan dalam sebuah perusahaan memiliki tujuan tersendiri, demikian pula dalam proses pembuatan laporan keuangan perusahaan.. Secara umum, laporan keuangan perusahaan merupakan media informasi keuangan sebuah perusahaan. Baik untuk informasi keuangan yang disusun pada kondisi khusus atau juga laporan yang disusun pada masa tertentu secara rutin. Untuk laporan yang disusun pada kondisi khusus ini, Teknik analisis data menggunakan teknik Structural Equation Modeling (SEM), melibatkan 1.245 karyawan PT Freeport Indonesia dan 412 sampel dikumpulkan dari karyawan. Hasil penelitian menunjukkan bahwa sistem informasi akuntansi berpengaruh pada struktur modal perusahaan. Analisis laporan keuangan dapat dilaksanakan secara efektif dan efisien dimana  laporan keuangan digunakan dengan metode dan teknik analisis untuk menentukan dan mengukur hubungan antara pos-pos dalam laporan keuangan, sehingga dapat diketahui perubahan-perubahan masing-masing pos bila diperbandingkan. Penelitian ini dilakukan di PT Freeport Indonesia yang berbasis di Papua.